Intervalidation of Dendrochronology and 14C Dating on a 700-yr Tree-Ring Sequence Originating from the Eastern Carpathians. Issue 5 (October 2019) - Sava, Gabriela O; Popa, Ionel; Sava, Tiberiu B; Meghea, Aurelia; Mănăilescu, Cristian; Ilie, Maria; Robu, Andrei; Tóth, Boglárka
ABSTRACT: We present a comparative study on a 700-yr sequence of dendrochronologically ordered tree-rings of Pinus cembra originating from Eastern Carpathians for the period AD 1009–1709. This period covers the solar minima of the Little Ice Age. The aim of this study was to assess the accuracy of our radiocarbon ( 14 C) determinations interpreted on the IntCal13 calibration data and to observe any apparent offsets. The 14 C measurements on single and double tree-rings were "wiggle-matched" to secure the dendrochronology cross-matching of all the Pinus cembra wood pieces. The results showed a very good agreement between the age datasets for four out of five wood trunks. However, for one of them a new cross-matching was performed after a quality assurance test, establishing an earlier 48-yr position, recommended by wiggle-matching Bayesian statistics and dendrochronological analysis. Following this adjustment, the quantification of the 14 C level variability with respect to the IntCal13 calibration curve was obtained by calculating Δ 14 C for all tree-ring samples. As a final conclusion, an insignificant 14 C concentration offset of –0.63 ± 3.76‰ was found for the Romanian samples.